Beyond Mechanism: Putting Life Back Into Biology, edited by Brian Henning, Adam Scarfe, and Dorion Sagan - Levin, Michael (Journal of Scientific Exploration, 2020)
A collection of essays on the foundations of biology and its connection to other sciences. Its lengthy and profound foreword by Stuart Kauffman, a major figure in the quantitative analysis of biological regulation at the system level, summarizes the intended main point: “we live not only in a world of webs of cause and effect, but webs of opportunities that enable, but do not cause, often in unforeseeable ways, the possibilities of becoming of the bio- sphere, let alone human life. But most importantly, I seek in this new worldview a re-enchantment of humanity”. (p. 1). To some extent, it’s meant as a reaction to what some perceive as a demoralizing aspects of the mechanistic paradigm that is driven by recent advances in the molecular bio-sciences: “I believe we are partially lost in modernity, seeking half-articulated, a pathway forward. Re-enchantment may be an essential part of this transformation.” (p. 1). I do not agree that the current situation is as bleak as many critics of the scientific mainstream suggest, but this book should appeal to anyone interested in the larger questions of biology no matter where they stand on this issue. All in all, it is an extremely enjoyable and valuable tour of important concepts and controversies.